The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0003489420965636
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Endoscopic Evaluation of Swallowing in Breastfeeding Infants With Laryngomalacia: Observed Clinical and Endoscopic Changes With Alteration of Infant Positioning at the Breast

Abstract: Objectives: This retrospective cohort study uses endoscopic assessment of the pharyngeal phase of swallowing in infants with laryngomalacia, to ascertain the impact of infant positioning on airway compromise and fluid dynamics during breastfeeding. The study aims to identify whether modification of infant positioning at the breast may improve the possibility of safe, successful breastfeeding in infants with laryngomalacia and concurrent breastfeeding difficulty. Methods: Twenty-three infants referred for noisy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Further analysis of the samples showed that three studies included only infants from the neonatal intensive care unit (NICU) [ 12 , 14 , 18 ], one focused on mechanically ventilated children [ 23 ], and two had a surgical focus [ 13 , 25 ]. Six studies related to a single diagnosis or symptom: Congenital Zika Syndrome [ 22 ], isolated Pierre-Robin sequence [ 15 ], laryngomalacia [ 16 ] and gastroesophageal reflux disease (GERD) [ 17 ], cerebral palsy [ 26 ], and prematurity [ 19 ]. The remaining 10 samples varied widely in terms of principal diagnosis [ 10 , 11 , 20 , 21 , 24 , 27 31 ] (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis of the samples showed that three studies included only infants from the neonatal intensive care unit (NICU) [ 12 , 14 , 18 ], one focused on mechanically ventilated children [ 23 ], and two had a surgical focus [ 13 , 25 ]. Six studies related to a single diagnosis or symptom: Congenital Zika Syndrome [ 22 ], isolated Pierre-Robin sequence [ 15 ], laryngomalacia [ 16 ] and gastroesophageal reflux disease (GERD) [ 17 ], cerebral palsy [ 26 ], and prematurity [ 19 ]. The remaining 10 samples varied widely in terms of principal diagnosis [ 10 , 11 , 20 , 21 , 24 , 27 31 ] (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, it was explicitly stated that feeding tubes were removed [ 12 , 18 ] or not removed [ 16 , 23 ]. Eighteen study protocols did not report on that topic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Descriptions of pediatric FEES routines were recently published by Miller, Schroeder, and Langmore [ 21 ] and Miller and Willging [ 22 ]. Modified procedures especially for breastfeeding [ 23 , 24 ] or for the neonatal intensive care unit (NICU) [ 25 , 26 ] have been tried and found to be safe. Objective methods for a transfer into a score such as the penetration-aspiration scale (PAS) according to Rosenbek [ 27 ] have not yet been validated for pediatric FEES, but are frequently in use.…”
Section: Introductionmentioning
confidence: 99%
“…Descriptions of pediatric FEES routines were recently published by Miller, Schroeder, and Langmore [21] and Miller and Willging [22]. Modified procedures especially for breastfeeding [23,24] or for the neonatal intensive care unit (NICU) [25,26] have been tried and found to be safe.…”
Section: Introductionmentioning
confidence: 99%